2018
DOI: 10.3389/fphys.2018.00216
|View full text |Cite
|
Sign up to set email alerts
|

Redox Aspects of Chaperones in Cardiac Function

Abstract: Molecular chaperones are stress proteins that allow the correct folding or unfolding as well as the assembly or disassembly of macromolecular cellular components. Changes in expression and post-translational modifications of chaperones have been linked to a number of age- and stress-related diseases including cancer, neurodegeneration, and cardiovascular diseases. Redox sensible post-translational modifications, such as S-nitrosylation, glutathionylation and phosphorylation of chaperone proteins have been repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 200 publications
(252 reference statements)
0
19
0
Order By: Relevance
“…Glutathionylation, like phosphorylation, can also regulate cell structure, signal transduction and metabolism, through reversible modulation of the structure and function of specific proteins (34,35). It has been shown that some chaperones are regulated by redox, including Hsp33, Asna1/TRC40, Hsp90, PDI and Hsp27 (36). In addition, Hsp70 and Hsp60 are susceptible to glutathionylation under oxidative stress conditions (36).…”
Section: Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathionylation, like phosphorylation, can also regulate cell structure, signal transduction and metabolism, through reversible modulation of the structure and function of specific proteins (34,35). It has been shown that some chaperones are regulated by redox, including Hsp33, Asna1/TRC40, Hsp90, PDI and Hsp27 (36). In addition, Hsp70 and Hsp60 are susceptible to glutathionylation under oxidative stress conditions (36).…”
Section: Structuresmentioning
confidence: 99%
“…It has been shown that some chaperones are regulated by redox, including Hsp33, Asna1/TRC40, Hsp90, PDI and Hsp27 (36). In addition, Hsp70 and Hsp60 are susceptible to glutathionylation under oxidative stress conditions (36). Glutathionylation of different members of the Hsp70 family has been detected in a variety of cells and tissues under oxidative conditions (21)(22)(23)(24)(25)(26)(27).…”
Section: Structuresmentioning
confidence: 99%
“…There are chaperones that are constitutively expressed (e.g., heat shock cognate 70, HSC70) and others, whose expression are induced by a cardiac stress [e.g., heat shock protein 70 (HSP70)] (Wu et al, 1985;Dworniczak and Mirault, 1987). Chaperones can protect cardiomyocytes against proteotoxicity and subsequent cell death during a stressful/pathological condition Tarone and Brancaccio, 2014;Penna et al, 2018). Indeed, overexpression of certain chaperones has protected hearts from cardiac disease Tarone and Brancaccio, 2014).…”
Section: Chaperonesmentioning
confidence: 99%
“…This review highlights the recent advances of arguably the most established PQC-regulating PTM, phosphorylation. Excellent reviews of the other PTMs have been described elsewhere (Christians and Benjamin, 2012;Scruggs et al, 2012;Wang et al, 2013;Penna et al, 2018; VerPlank and Goldberg, 2018). This review details the recent PQC phosphorylations that have been identified ( Supplementary Table 1), especially those with influential roles in cardiac pathophysiology and some ubiquitous signaling pathways, and that can be clinically interrogated.…”
Section: Introductionmentioning
confidence: 99%
“…Chaperones have been originally discovered as induced by hyperthermia, whereby the name of heat shock proteins (HSPs) has been attributed to a number of chaperones (Schlesinger, 1990). Later, it became clear that several chaperones are induced upon different types of stress stimuli, including oxidative stress, pathogen infection, mechanical stress, hypoxic conditions, and ischemia (Sbroggio et al, 2008;Tarone and Brancaccio, 2014;Sorge and Brancaccio, 2016;Penna et al, 2018). Chaperones are divided in different subfamilies depending on their structure, molecular weight and on their ability to hydrolyze ATP (Macario and Conway de Macario, 2005;Kampinga et al, 2009).…”
Section: Intracellular Chaperonesmentioning
confidence: 99%